2016
DOI: 10.3923/jms.2017.17.21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neutrophils-lymphocytes Ratio and Procalcitonin Parameters in Sepsis Patient Treated in Intensive Care Unit Dr. Wahidin Hospital, Makassar, Indonesia

Abstract: Neutrophils-lymphocytes ratio (NLR) is regarded as a cheap, simple and promising parameter to predict sepsis severity. This study was aimed to compare NLR and procalcitonin (PCT) parameters and its correlation with acute physiology and chronic health evaluation (APACHE) II scoring system in sepsis and severe patients. This retrospective study investigated 65 sepsis patients data in the medical record that been treated in Intensive Care Unit (ICU) in the last 2015 at Dr. Wahidin Sudirohusodo Hospital Makassar. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 12 publications
4
16
0
4
Order By: Relevance
“…Both CRP and procalcitonin were found to have significant associations with NLR. Similar results have been previously proposed by authors, such as Ljungström et al and Xu et al, for CRP and by Merik et al and Arif et al for procalcitonin [ 21 - 24 ]. Most of the above-mentioned studies showed these associations to be of prognostic value as well [ 21 , 23 - 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both CRP and procalcitonin were found to have significant associations with NLR. Similar results have been previously proposed by authors, such as Ljungström et al and Xu et al, for CRP and by Merik et al and Arif et al for procalcitonin [ 21 - 24 ]. Most of the above-mentioned studies showed these associations to be of prognostic value as well [ 21 , 23 - 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been previously proposed by authors, such as Ljungström et al and Xu et al, for CRP and by Merik et al and Arif et al for procalcitonin [ 21 - 24 ]. Most of the above-mentioned studies showed these associations to be of prognostic value as well [ 21 , 23 - 24 ]. Zheng et al, however, reported CRP and procalcitonin to be better biomarkers than NLR for predicting sepsis [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…The neutrophil to lymphocyte ratio (NLR), is an inflammatory mediator used as predictor of systemic inflammation [1]. Numerous studies conducted around globe have reported about neutrophil to lymphocyte ratio (NLR) as a predictor of prognosis in a variety of cancers (breast, ovary, lung), cardiovascular disorders (coronary procedures and coronary artery bypass grafting), infectious disorders (community-acquired pneumonia, corona) and sepsis in general [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil to lymphocyte ratio (NLR) is promptly accessible parameter calibrated entirely through a report of complete blood count (CBC); it is economical and simple as compared to the rest of mediators making it potential diagnostic criterion [2][3][4]. Neutrophil to lymphocyte ratio (NLR) is a prominent predictor of severity of disease, if high levels are detected it determines poor prognosis and high mortality within patients of intensive care units [3][4][5]. Elevating levels of neutrophil to lymphocyte ratio (NLR) projects towards the prediction of mortality among sufferers of acute coronary syndrome, intracerebral hemorrhage, polymyositis, dermatomyositis, and cancers [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, CRP can increase in both infectious and noninfectious diseases and, even though procalcitonin has a well-defined role as a sepsis biomarker, it has inconsistent and variable results for the diagnosis of infectious sepsis, not to mention it is expensive to assess [15,16]. Recently, studies have been undertaken on inflammatory markers obtained from complete blood counts (CBCs) with simple calculations for early recognition of infection and assessing treatment response [17][18][19][20][21][22]. Inflammatory markers obtained by CBCs, such as the NLR, PLR, platelet to mean platelet volume (MPV), have been assessed in different disease groups for their association with hospital mortality [12,13,22,23].…”
Section: Introductionmentioning
confidence: 99%